Pioneering advantage in generic drug competition. Issue 2 (27th May 2014) - Yu, Yu; Gupta, Sachin
Abstract : Purpose: – The purpose of this paper is to take a close look at competition among the generic entrants during the first three years after patent expiration and examine whether there is a first mover advantage. Pharmaceutical markets experience the entry of numerous generic firms upon expiration of the brand firm's patent. Design/methodology/approach: – A random effect nested logit model of competition that allows for competition between the brand drug and generics, and among multiple generic drugs is specified. The model accommodates the effects of prices, detailing, sampling, journal advertising, time-in-market and molecule-specific characteristics. The model is estimated on cross-section time-series data for 49 molecules in which the brand drug lost patent exclusivity between 1992 and 2000. Findings: – Strong evidence that the early generic entrant enjoys a substantial market share and profit advantage over the second and the third entrants, after controlling for differences in marketing activities was found. In addition, evidence suggesting that the advantage is due to the response of the retail pharmacy channel and due to differential effectiveness of advertising and pricing between earlier versus later entrants was found. Originality/value: – This paper is the first to empirically model first mover advantage among undifferentiated products. The findings are useful for regulators in pharmaceutical and healthcare industries. They can also shed light on other industries where there is little or no quality differentiation, such as commodity trading, open-source software distribution and online banking.